Hospital School Students' Academic Motivation and Support Needs: A Self-Determination Perspective - Mombaers, Tine; Donche, Vincent (Frontiers in Education, 2020)
In contrast with the plethora of studies on the academic motivation of regular students in regular educational settings, this study aims to shed light on the motivation and educational support needs of chronically ill children in hospital schools. This in-depth qualitative study seeks to explore whether the expected motivational dimensions central in SDT research are present in this specific population and setting and if the expected relationships with 'needs' are present. In contrast with research on academic motivation and needs in common classrooms, research on hospital schools is very scarce. Using the theoretical framework of self-determination theory, we investigated the presence of different types of motivation linked with ABC. More specifically, we investigated students' motivational types linked with the educational support needs that they expect their hospital school teacher(s) to address. A purposive selected sample of six students with severe chronic or long-term illnesses from three different hospital schools in Flanders (Belgium) was interviewed, using elicitation techniques to further deepen the data collection. Despite their chronic illnesses, all participating students were academically motivated, although some students indicated that not feeling well could cause temporary motivational regression. We were able to distinguish differences in motivation and expected need support. More controlled motivated students from the university hospital schools indicated a preference for support in terms of relatedness. More autonomously motivated students from a hospital school within a revalidation center showed more autonomous motivation and preferred competence support, instead of the autonomy-support that would be expected according to self-determination theory.